2016
DOI: 10.1002/jssc.201500960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stationary phases that provide group recognition for polychlorinated biphenyls by porogenic fragment template imprinting

Abstract: Molecular recognition based on imprinted polymers results from the polymerization of functional monomers and cross-linkers in the presence of a target analyte (i.e. template), with subsequent removal of the template to create synthetic binding sites. However, complete removal of the template is difficult to achieve, thereby leading to template leaching, which adversely affects real-world analytical applications. To overcome this challenge, the present study utilizes porogenic fragment template imprinting techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recently, differences between MIPs and NIPs in terms of pores interconnectivity has been reported by Neusser et al 41 The group investigated the porosity of MIPs via 3D FIB/SEM tomography, whereby MIPs were found to have more of their pores interconnected to each other compared to smaller interconnection areas noted for NIPs ( Figure 4). The pore volume and pore area of MIPs was found to be approximately 34% and 35% higher compared to that of the NIPs.…”
Section: Ifmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, differences between MIPs and NIPs in terms of pores interconnectivity has been reported by Neusser et al 41 The group investigated the porosity of MIPs via 3D FIB/SEM tomography, whereby MIPs were found to have more of their pores interconnected to each other compared to smaller interconnection areas noted for NIPs ( Figure 4). The pore volume and pore area of MIPs was found to be approximately 34% and 35% higher compared to that of the NIPs.…”
Section: Ifmentioning
confidence: 85%
“…Pores in red color in (A) and (B) represent pore space. In (C) and (D), large interconnected pore spaces is marked with the same color, whereby molecularly imprinted polymer pore network in (C) reveal large interconnected areas compared to D; Reproduced from Reference 41 Copyright 2017, with permission form the Royal Society of Chemistry)…”
Section: Molecular Imprinting Processmentioning
confidence: 99%
“…The xylene imprinted polymers (XIPs) clearly outperformed conventional C 18 stationary phase materials, while demonstrating enhanced recognition properties for PCBs with at least 2 chlorine atoms at the meta, and para-position. 94 This study also indicated that toluene could also serve as a potential dummy template for imprinting PCBs, as polymers synthesized using only toluene gave excellent results during preconcentration studies reflected in enhanced retention factors compared to polymers synthesized using a template and a low amount of functional monomer. The imprinting effect realized by using alkylbenzenes was confirmed by the resulting imprinting factor of 1.56 vs. non-imprinted polymers (NIPs) synthesized using cyclohexane.…”
Section: Polychlorinated Biphenyls and Hydroxy-polychlorinated Biphenylsmentioning
confidence: 67%
“…Time consuming optimization of conditions for their preparation, which include selection of compounds of polymerization mixture (monomer, crosslinking agent and porogen), their ratio, as well as reaction conditions (temperature and time of polymerization) to form polymer with required properties (high sorption capacity, selectivity, morphology) (Cheong et al 2012). Due to their properties, MIPs have great potential in analytical applications, in biosensors (Nguy et al 2017;Selvolini and Marrazza 2017), capillary electrophoresis (Alenazi et al 2015;Giovannoli et al 2018), high performance liquid chromatography (Ndunda and Mizaikoff 2016;Yang et al 2018), supercritical fluid chromatography (Ansell et al 2012), or even in sample treatment procedures such as solid phase extraction (Bujak et al 2016;Lucci et al 2017), solid phase microextraction (Szultka et al 2013;Turiel et al 2016) and stir bar sorptive extraction (Fan et al 2016;Tang et al 2018).…”
Section: Introductionmentioning
confidence: 99%